The Daimon in Hellenistic Astrology - László, Levente (Aestimatio)

(untitled) (Institute for Research in Classical Philosophy and Science, 2020)
A discussion of Dorian Greenbaum’s The Daimon in Hellenistic Astrology: Origins and Influence.